Dielectrophoretic characterization and separation of monocytes and macrophages using 3D carbon‐electrodes. Issue 2 (6th November 2018) - Elitas, Meltem; Yildizhan, Yagmur; Islam, Monsur; Martinez‐Duarte, Rodrigo; Ozkazanc, Didem
Abstract: Monocyte heterogeneity and its prevalence are revealed as indicator of several human diseases ranking from cardiovascular diseases to rheumatoid arthritis, chronic kidney diseases, autoimmune multiple sclerosis, and stroke injuries. When monocytes and macrophages are characterized and isolated with preserved genetic, phenotypic and functional properties, they can be used as label‐free biomarkers for precise diagnostics and treatment of various diseases. Here, the dielectrophoretic responses of the monocytes and macrophages were examined. We present 3D carbon‐electrode dielectrophoresis (carbon‐DEP) as a separation tool for U937 monocytes and U937 monocyte‐differentiated macrophages. The carbon‐electrodes advanced the usability and throughput of DEP separation, presented wider electrochemical stability. Using the 3D carbon‐DEP chip, we first identified the selective positive and negative DEP responses and specific crossover frequencies of monocytes and macrophages as their signatures for separation. The crossover frequency of monocytes and macrophages was 17 and 30 kHz, respectively. Next, we separated monocyte and macrophage subpopulations using their specific dielectrophoretic responses. Afterward, we used a fluorescence‐activated cell sorter to confirm our results. Finally, we enriched 70% of monocyte cells from the mixed cell population, in other words, concentration of monocyte cells to macrophage cells was five times increased, using the 30‐kHz, 10‐Vpp electric field and 1 μL/min flow rate.